If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -9 = 7x + 4 Reorder the terms: -9 + 2x = 7x + 4 Reorder the terms: -9 + 2x = 4 + 7x Solving -9 + 2x = 4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -9 + 2x + -7x = 4 + 7x + -7x Combine like terms: 2x + -7x = -5x -9 + -5x = 4 + 7x + -7x Combine like terms: 7x + -7x = 0 -9 + -5x = 4 + 0 -9 + -5x = 4 Add '9' to each side of the equation. -9 + 9 + -5x = 4 + 9 Combine like terms: -9 + 9 = 0 0 + -5x = 4 + 9 -5x = 4 + 9 Combine like terms: 4 + 9 = 13 -5x = 13 Divide each side by '-5'. x = -2.6 Simplifying x = -2.6
| 10x^2+6x-99=0 | | 10x^2+6x-99=100 | | 4y^2+3/2y-2=0 | | 7x^2-5=100 | | 235-5x=40x+20 | | 21p+52=10 | | 5/(2w+12)+1=-8/(w+6) | | 3x+36=10x-41# | | 7/w-2=-8+(5/w+1) | | 6x/x+1+2/x-3=6 | | 12r+24=-12 | | x^2-5x+22=0 | | 16-9u=20 | | 3x+3(x-2)+3= | | (-3)-(-2)+(-1)(-1)(2)= | | (4y+1)(8-y)=0 | | x^2+25x+20=0 | | 5d+-25=-75 | | 6x+56=14x | | 3x+72=12x | | (x-2)(4x+5)=9 | | 45-15=-10m | | 2ln(x-7)=4 | | 4x+30=12x-15 | | 13-9x=198-44x | | 4k^2-9k-5=0 | | 2(4x-1)=22 | | 11x-31=7x+4 | | y-1/y-3=(y-1/y+5)+1 | | 17/3x+3/5=8/3x | | X^1/3-2=0 | | 2x^4-2=160 |